Filmes de poliuretana híbridos biobaseados a partir de quitosana e óleo de mamona - Assis, Jordanna Fernandes (Universidade Federal de São Carlos, 2025)
This study aimed to develop hybrid bio-based polyurethane-urea (PUU) films derived from castor oil (CO) and chitosan (CS), using hexamethylene diisocyanate–iminooxadiazinedione (HDI-t-Im-Ox) in an innovative solvent- and catalyst-free process with concomitant film formation. This approach contributes to the advancement of sustainable polyurethanes by exploring the incorporation of natural precursors as alternatives to conventional PUs, which are generally associated with negative environmental impacts, thereby expanding the potential applications of these materials in biomaterials, functional coatings, adhesives, and smart packaging systems. The chemical incorporation of CS was confirmed by FTIR, evidencing the formation of urethane and urea linkages and proving its role as a reactive polyol. X-ray diffraction indicated an increase in the crystallinity index in CS-containing formulations. Thermogravimetric analyses revealed thermal stability of all films up to approximately 250 °C, with onset degradation temperatures (Tonset) ranging from 250 to 316 °C. Dynamic mechanical analyses showed a significant increase in the glass transition temperature (Tg) and in mechanical stiffness in the CS-containing films, evidencing the higher structural complexity of the formed hybrid networks. The PUCO control film exhibited a sub-ambient Tg (-1 °C), whereas CS-containing films showed Tg values close to room temperature (28-31 °C), and a markedly high Tg of 136 °C was observed for the PU100CSL formulation. Mechanical tests indicated that PU100CSL presented the highest tensile strength (17.3 MPa) and Young’s modulus (446 MPa), accompanied by low elongation at break (5%), while the other CS-containing formulations exhibited a moderate increase in stiffness compared to PUCO. Contact angle analyses revealed moderate variations in wettability, and zeta potential measurements confirmed surface stability over a wide pH range. All films exhibited satisfactory biocompatibility in cell viability assays. These results demonstrate that chitosan effectively acts as a reactive polyol, promoting the formation of hybrid PUU networks with tunable thermal, mechanical, and surface properties, reinforcing the potential of these bio-based films for applications in biomaterials, functional coatings, and controlled release systems.
Formation of bio-based films during the synthesis of polyuthane-urea from chitosan
Keywords: Poliuretanas bio-baseadas; Óleo de mamona; Quitosana; Filmes híbridos; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA; 12. Consumo e Produção Responsáveis; 9. Indústria, Inovação e Infraestrutura